Two sides are equal in an isosceles triangle. This means that the angle both sides make with the third side must be the same. Since the angles in a triangle add up to 180°, you can subtract 110° from 180° and divide your answer by two. The resulting number will be the measure of each of the two unknown angles
Hello from MrBillDoesMath!
Answer:
(x+2) ( x^2 + 3)
Discussion:
x^3 + 2x^2 + 3x + 6 =
(
x^3 + 2x^2) + (3x + 6) = => factor "x^2" from the first term; factor 3
from the second term
x^2( x + 2) + 3( x+2) = => factor (x+2) from each term
(x+2) ( x^2 + 3)
Thank you,
MrB